The Power of Integrated Audits for Ethical and Effective Risk Management - Wahyuni, Wahyuni; Arfang, Muhammad Ayyub; Faisal, Fauzan Ashari; Supirman, Supirman; Sari, Sucipta Anugra (Advances in Managerial Auditing Research, 2024)
The purpose of this study is to explore the role of integrated audits in promoting ethical conduct and effective risk management within organizations. The research design and methodology involve a qualitative approach based on a systematic literature review. Relevant literature from academic journals, books, and conference proceedings is analyzed to identify key concepts and trends related to integrated audits and ethical risk management. The findings and discussion highlight the multifaceted benefits of integrated audits, including their ability to provide organizations with a holistic understanding of their risk landscape and to embed ethical considerations into decision-making processes. The implications of this research suggest that integrated audits offer organizations a comprehensive approach to navigate uncertainties while upholding ethical standards, with significant implications for organizational resilience and stakeholder trust.